Tingkat Ketanggapan Pelayanan Kesehatan Rawat Inap di Indonesia - Lukman Prayitno; Primasari Syam; Hendrianto Trisnowibowo; Mugeni Sugiharto (Buletin Penelitian Sistem Kesehatan, 2020)
Responsiveness of the health system in in-patient services is closely related to patient's reasonable expectations of non-clinical aspects for inpatient care. A comfortable patient can straight influence level of responsiveness. This study aimed to determine level of in-patient responsiveness and significance of respondent characteristics on eight responsiveness domains. It was a further analysis of the Responsiveness Survey of 2017. A Cross-Sectional design with a quantitative approach and has performed in 34 provinces in Indonesia. Most mean responsiveness scores were in range of good scores. Moreover, Lowest score was quality basic amenities domain, while highest score was confidentiality domain. Level of in-patient responsiveness was good category (8,05). Each characteristic has significantly correlated with one or more responsiveness domains. We can increase in-patient responsiveness value that less than 8,0 through improving three responsiveness domains, i.e., dignity, access to social network, and provider choice. Abstrak Ketanggapan rawat inap sistem kesehatan berkaitan dengan harapan logis pasien terhadap aspek non medis. Level Ketanggapan dapat secara langsung mempengaruhi kenyamanan pasien. Penelitian bertujuan mengetahui level Ketanggapan rawat inap dan signifikansi karakteristik responden terhadap 8 domain Ketanggapan. Penelitian ini merupakan analisa lanjut data survei Ketanggapan tahun 2017. Metode penelitian adalah cross-sectional dengan pendekatan kuantitatif. Survei ini dilakukan di 34 provinsi di Indonesia. Semua rerata skor Ketanggapan berada pada rentang skor baik. Nilai skor yang paling rendah adalah domain quality basic amenities. Sedangkan nilai skor yang paling tinggi adalah domain confidentiality. Level Ketanggapan rawat inap adalah 8,05 dan masuk kategori baik. Setiap karakteristik mempunyai hubungan signifikan dengan satu atau lebih domain Ketanggapan. Nilai Ketanggapan rawat inap bisa ditingkatkan dengan memperbaiki 3 domain Responsiveness, yaitu Dignity, Acces to social network, Choice of provider.